Perencanaan Kurikulum Yang Selaras Dengan Profil Lulusan - Eli Sabrifha; Jira Indriani (CV. SINAR HOWUHOWU, 2026)
Curriculum planning aligned with graduate profiles is a fundamental aspect of delivering quality education that is relevant to learners’ needs and the demands of society and the labor market. This article aims to examine the concepts, principles, and strategies of curriculum planning oriented toward achieving graduate profiles as the final outcomes of the educational process. This study employs a literature review method by analyzing various scientific sources, including books, journal articles, and relevant educational policy documents. The findings indicate that alignment between the curriculum and graduate profiles can be achieved through the formulation of clear learning outcomes, the integration of knowledge, skills, and attitudes, and the implementation of contextual and student-centered learning approaches. Furthermore, continuous curriculum evaluation is essential to ensure consistency between educational objectives and the competencies of graduates. Through systematic curriculum planning oriented toward graduate profiles, educational institutions are expected to produce competent, adaptive, and competitive graduates.